Three-dimensional facial analyses of Indian and Malaysian women - Preethi Kusugal; Zarir Ruttonji; Roopa Gowda; Ladusingh Rajpurohit; Pritam Lad; Ritu (Wolters Kluwer Medknow Publications, 2015)
Context: Facial measurements serve as a valuable tool in the treatment planning of maxillofacial rehabilitation, orthodontic treatment, and orthognathic surgeries. The esthetic guidelines of face are still based on neoclassical canons, which were used in the ancient art. These canons are considered to be highly subjective, and there is ample evidence in the literature, which raises such questions as whether or not these canons can be applied for the modern population. Aims: This study was carried out to analyze the facial features of Indian and Malaysian women by using three-dimensional (3D) scanner and thus determine the prevalence of neoclassical facial esthetic canons in both the groups. Subjects and Methods: The study was carried out on 60 women in the age range of 18-25 years, out of whom 30 were Indian and 30 Malaysian. As many as 16 facial measurements were taken by using a noncontact 3D scanner. Statistical Analysis Used: Unpaired t-test was used for comparison of facial measurements between Indian and Malaysian females. Two-tailed Fisher exact test was used to determine the prevalence of neoclassical canons. Results: Orbital Canon was prevalent in 80% of Malaysian women; the same was found only in 16% of Indian women (P = 0.00013). About 43% of Malaysian women exhibited orbitonasal canon (P = 0.0470) whereas nasoaural canon was prevalent in 73% of Malaysian and 33% of Indian women (P = 0.0068). Conclusions: Orbital, orbitonasal, and nasoaural canon were more prevalent in Malaysian women. Facial profile canon, nasooral, and nasofacial canons were not seen in either group. Though some canons provide guidelines in esthetic analyses of face, complete reliance on these canons is not justifiable.